Analisis Wacana Pesan Dakwah pada Film Cinta dalam Ukhwah - Yasyifa Fajaria Nursyamsi; Dindin Sholahudin; Tata Sukayat (Department of Islamic Communication and Broadcasting, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2017)
This research describes the message of dakwah clarity of discourse. Film as a medium of da'wah becomes a thing to be examined both in terms of meaning and production, especially in the field of I'lam. Its presence in the scholarship of da'wah can be a reference that supports the spread of Islamic values. This qualitative research uses the theory of discourse analysis according to Teun Van Djik with the concept of 'social cognition' which is adapted from the social psychology approach to explain the structure and process of forming a text. The results of the film Love in this ukhuwah got three main conclusions: first the text of this film contain Message da'wah with the topic of tolerance, ukhuwah and inclusivism. Second, the social cognition of the author's personal experience affects how text scenarios are produced. Thirdly, the social context of Islamic societal issues is raised as 'conflict and anti-climax' in dialogue on scenarios and film texts produced. The story presented in the film is lifted from the discourse through psychosocial approaches, constructing discourses about critical attitudes and tabayun against this Jewish strategy as a moral message. Penelitian ini memaparkan pesan dakwah dari kejelasan wacananya. Penelitian kualitatif ini menggunakan teori analisis wacana menurut Teun Van Djik dengan konsep ‘kognisi sosial’ istilah yang disadur dari pendekatan psikologi sosial untuk menjelaskan struktur dan proses terbentuk suatu teks. Hasil penelitian di film Cinta dalam Ukhuwah ini didapatkan tiga kesimpulan utama: pertama secara teks film ini mengandung Pesan dakwah dengan topik toleransi, ukhuwah dan inklusivisme. Kedua, kognisi sosial pengalaman pribadi penulis mempengaruhi bagaimana teks skenario diproduksi. Ketiga, konteks sosial permasalahan masyarakat Islam diangkat sebagai ‘konflik dan anti klimaks’ dalam dialog pada teks skenario dan film yang diproduksi. Cerita yang disampaikan dalam film di angkat dari wacana melalui pendekatan psikososial, mengkontruksi wacana tentang sikap kritis dan tabayun terhadap strategi yahudi ini sebagai pesan moral.